Rancang Bangun Mesin Cetak Centrifugal Casting untuk Pembuatan Pipa Komposit Geopolimer - Jamiatul Akmal; Arisandi Arisandi; Ahmad Suudi; Asnawi Lubis; Novri Tanti (Politeknik Negeri Padang, 2022)
In the field of materials engineering, various types of advanced materials have been found. This must also be accompanied by technological advances in the production process. Centrifugal casting is an effective method for casting cylindrical objects such as pipes and pressure vessels. In this research, a centrifugal casting machine is designed and made. The design process follows the steps proposed by Pahl and Beitz, starting from requirements identification, concept design, layout and analysis to the fabrication method. Furthermore, this machine was tested for casting geopolymer composite pipes. From the test results it is stated that this machine works well and can cast pipe samples at various speeds. Furthermore, the sample is cut into a three-point bending test specimen. From the test results obtained bending strength of about 50 MPa (1500 rpm tube rotation) and about 36 MPa (1200 rpm tube rotation). Thus, it is concluded that the higher the tube rotation, the higher the quality of the resulting product.